Activation of Aromatic C−F Bonds by a N‐Heterocyclic Olefin (NHO). Issue 27 (28th April 2020) - Mandal, Debdeep; Chandra, Shubhadeep; Neuman, Nicolás I.; Mahata, Alok; Sarkar, Arighna; Kundu, Abhinanda; Anga, Srinivas; Rawat, Hemant; Schulzke, Carola; Mote, Kaustubh R.; Sarkar, Biprajit; Chandrasekhar, Vadapalli; et al.
Abstract: A N‐heterocyclic olefin (NHO), a terminal alkene selectively activates aromatic C−F bonds without the need of any additional catalyst. As a result, a straightforward methodology was developed for the formation of different fluoroaryl‐substituted alkenes in which the central carbon–carbon double bond is in a twisted geometry. Abstract : NHO activation : The activation of aromatic C−F bonds by N‐heterocyclic olefin (NHO) occurs without the need of any additional catalyst. As a result, a straightforward methodology was developed for the formation of different fluoroaryl‐substituted alkenes.